Evaluation of early clinical features and outcomes after dental implant placement (Annals of Medical Research, 2021)
Aim: It was aimed to evaluate implant success and outcomes in the first 3 months after implant placement. Material and Methods: Totally, 75 patients with 123 dental implants that were placed different areas in the maxilla and mandible. Demographic and clinical data of the patients such as gender implant brand and duration of surgery was collected and analyzed during the first 3 months after implant placement. Results: 45 (60%) females and 30 (40%) males, aged between 20 and 76 years were included. The mean age was 46.17±14.79 years. Dehiscence of the flap was in 22 patients after surgical procedure. In addition, one patient had implant failure and one patient had suppuration. Conclusion: Within limitation of this study, implant success rate was high in early period. It was detected that insertion of dental implants was mostly located in the posterior region of the maxilla and mandible.Keywords: Dental implant; early outcomes; success
Keywords: Dental implant; early outcomes; success